Crucibles of leadership: how to learn from experience to become a great leader - "Thomas, Robert J." (Boston, 2008)
Experience may be a leader's best teacher--but there's a hitch. Two people can have identical experiences, but one blossoms while the other is depleted. The same can be said for any pair of fired CEOs, unsuccessful political candidates, or rookie supervisors. In Crucibles of Leadership, Robert J. Thomas concludes that what matters most is what one makes of experience, particularly the traumatic and often unplanned crucible events that challenge one's identity as a leader. What distinguishes leaders who grow through a crucible experience? Their approach to learning. Like accomplished athletes or artists, they practice as strenuously as they perform. And because the line between performance and practice is often hard to discern, they learn how to practice while they perform. But theirs is no ordinary practice. It's a regimen tailored to individual aspirations, motivations, and learning styles--a Personal Learning Strategy. Building on insightful and moving stories told by accomplished leaders, Thomas offers probing self-assessments and innovative tools designed to help you develop your own Personal Learning Strategy. Provocative and original, with examples drawn from business and politics as well as from the inner workings of the Mormon Church and the Hell's Angels, Thomas's book will revolutionize the way you think about leadership and learning.
Keywords: Leadership